A Comparison between Physicians, Nurses and the Immediate Families of Patients` Attitudes towards Family Members Presence during CPR - Z Taraghi; E Ilail; T yaghoobi; F noroozinejad; F Naseri; S K Baghernejad; R A mohammadpour (Tehran University of Medical Sciences, 2013)
Abstract Background: There are different attitudes about family presence during CPR. This study was conducted in order to compare the attitudes of physicians, nurses and patients` immediate family towards presence of family members during adult resuscitation in teaching hospitals of Mazandaran University of Medical Sciences. Material and Methods: In this descriptive survey, the attitudes of 120 physicians, 200 nurses and 148 patients` immediate family were compared. Random stratified sampling was used as the sampling method. The data were collected using a self-developed questionnaire which its validity and reliability had been confirmed by "Content validity" and "Test-Retest" respectively (r=0/83).This questionnaire included some questions about demographic characteristics, positive and negative experiences and the attitudes towards family presence during CPR. Data were analyzed using Chi-square x2 and Fisher tests by the SPSS 16 software. Results: The majority of physicians and nurses (92/5% physicians, 80%nurses) believed that family presence during CPR is harmful. Fisher exact test showed significant difference between physicians and nurses views (x2=9.037 df=1 p value=0/002). The most important reason of negative attitudes of physicians and nurses has been interference of family members in CPR (90/8% physicians, 86/5% nurses).Less than half of the patients` immediate family (48%) wanted to be present during the CPR. There was a significant difference between attitudes of patients` immediate family and physicians and nurses (p=000) Conclusion: Regarding differences between physicians, nurses and patients` immediate family` attitudes towards family presence during CPR, it would be better to provide a determined plan identifying the family presence`s conditions during CPR in every hospital respectively.